(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The survey showed sample opinions of officials in the general company for vegetable oils industry, and the statement of the order of the effect of these dimensions depending on the degree of importance, the questionnaire was used as a key tool in collecting data and information of the sample consisted of 30 officials, arithmetic mean, standard deviation, percentages, Spearman correlation coefficient and the global statistical analysis as a statistical methods that based on statistical program (SPSS), The researcher came to several conclusions, most important that there is high agreement by the respondents of the importance of the dimensions of building a mental picture of the company and to attract the consumer’s attention, Also research found that the dimensions of build a mental picture of the company’s was influence in attracting the attention of the consumer and the percentage of their contribution to the interpretation of the overall disparity is 78.7% which is a good percentage, the arrangement dimensional descending order of importance in effect as follows (behavioral dimension, the social dimension, the dimension of knowledge and emotional dimension).